2021
DOI: 10.1126/sciadv.abh1489
|View full text |Cite
|
Sign up to set email alerts
|

Rampant prophage movement among transient competitors drives rapid adaptation during infection

Abstract: Interactions between bacteria, their close competitors, and viral parasites are common in infections, but understanding of these eco-evolutionary dynamics is limited. Most examples of adaptations caused by phage lysogeny are through the acquisition of new genes. However, integrated prophages can also insert into functional genes and impart a fitness benefit by disrupting their expression, a process called active lysogeny. Here, we show that active lysogeny can fuel rapid, parallel adaptations in establishing a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 103 publications
(141 reference statements)
0
12
0
Order By: Relevance
“…Prophages are commonly harbored by bacteria, and the auxiliary metabolic genes can alter microbial physiology and confer additional benefits such as enhanced metabolism, elevated biofilm EPS production, and immunity to phages. However, upon exposure to external stressors, the dormant prophage can be stimulated to enter the lytic cycle, which produces more infectious phage particles at the lysis of their hosts . The lysate of E.…”
Section: Resultsmentioning
confidence: 99%
“…Prophages are commonly harbored by bacteria, and the auxiliary metabolic genes can alter microbial physiology and confer additional benefits such as enhanced metabolism, elevated biofilm EPS production, and immunity to phages. However, upon exposure to external stressors, the dormant prophage can be stimulated to enter the lytic cycle, which produces more infectious phage particles at the lysis of their hosts . The lysate of E.…”
Section: Resultsmentioning
confidence: 99%
“…RSCVs form colonies with a wrinkled appearance, are more prone to aggregation and surface attachment, and exhibit increased exopolysaccharide (EPS) production ( Starkey et al, 2009 ). RSCVs are associated with hyper-biofilm formation and tend to characterize poorer clinical outcomes as repeatedly seen in chronic infections ( Marshall et al, 2021 ). Some studies also suggest that the appearance of RSCVs may be a response to extended antibiotic therapy ( Starkey et al, 2009 ).…”
Section: Pao1 and Pa14 Virulence Determinant Differencesmentioning
confidence: 99%
“…Some studies also suggest that the appearance of RSCVs may be a response to extended antibiotic therapy ( Starkey et al, 2009 ). A study found that RSCVs accounted for 30% of PA14 antibiotic-resistant colonies and also formed among PAO1 populations ( Drenkard and Ausubel, 2002 ; Pu et al, 2018 ; Marshall et al, 2021 ).…”
Section: Pao1 and Pa14 Virulence Determinant Differencesmentioning
confidence: 99%
“…As bacteria can only undergo homologous recombination with closely related individuals, usually of the same species [ 65 ], the low number of coexisting strains of any given species within a given microbiome [ 11 , 37 ] limits the supply of alternative alleles for any given gene (horizontal gene transfer is a distinct process from recombination, which brings in new alleles of existing genes). Thus, even if a bacterial strain is naturally competent [ 66 ] or has the capacity for phage-mediated gene transfer [ 67 , 68 ], the potential for bringing in new alleles via recombination is low; most recombination events will occur within members of the same strain. This low level of recombination means that measures of nucleotide diversity and adaptive potential are decoupled; while a two-strain population has access to a larger genotypic space than a single-strain population, this increase is not proportional to the corresponding change in π.…”
Section: Asexual Within-host Populations Evolve Differently To Classi...mentioning
confidence: 99%